POLITIK HUKUM KEWENANGAN DAERAH YANG BERCIRI KEPULAUAN - Bahri; Meda Hanizar, Simbolon (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
Legal politics is the direction of the government's official policy regarding the rules that will be implemented both in making new rules and replacing old laws to achieve state goals. For that to happen, law needs to use support and as the basis for state life to claim and protect people's rights. , rules similar to those claimed by the constitution. This is what is claimed by the social contract between citizens as reflected in the constitution. The type of research used by the author is in accordance with the problems in this study, namely the type of library research. The research conducted is descriptive analysis, namely a study aimed at obtaining suggestions regarding what to do to overcome a particular problem. In this new view of citizen sovereignty, it must still be guaranteed that it is the people who are actually the owners of the State with all their authority to carry out all the functions of State power, both in the legislative, executive and judicial fields. It is the people who have the authority to plan, organize, implement, and supervise and evaluate the application of the functions of that power. Keywords: law, Legal Policy, and Local Goverment